2022
DOI: 10.1111/mec.16776
|View full text |Cite|
|
Sign up to set email alerts
|

Genome‐scale signatures of adaptive gene expression changes in an invasive seaweed Gracilaria vermiculophylla

Abstract: Invasive species can successfully and rapidly colonize new niches and expand ranges via founder effects and enhanced tolerance towards environmental stresses. However, the underpinning molecular mechanisms (i.e., gene expression changes) facilitating rapid adaptation to harsh environments are still poorly understood. The red seaweed Gracilaria vermiculophylla, which is native to the northwest Pacific but invaded North American and European coastal habitats over the last 100 years, provides an excellent model t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…Indicator genera associated with elevated temperature suggest that warming supports the growth of potentially pathogenic bacteria. A recent study [ 63 ] showed that some adaptive changes in gene expression regulated by microRNA occurred after G. vermiculophylla invaded new areas in the European and North American coasts, allowing us to hypothesize that epibacteria are likely involved in such molecular interaction networks between the host G. vermiculophylla and associated microbiota. Future studies can focus on testing the epigenetic processes mediated by the epibacterial community structure of G. vermiculophylla at elevated temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Indicator genera associated with elevated temperature suggest that warming supports the growth of potentially pathogenic bacteria. A recent study [ 63 ] showed that some adaptive changes in gene expression regulated by microRNA occurred after G. vermiculophylla invaded new areas in the European and North American coasts, allowing us to hypothesize that epibacteria are likely involved in such molecular interaction networks between the host G. vermiculophylla and associated microbiota. Future studies can focus on testing the epigenetic processes mediated by the epibacterial community structure of G. vermiculophylla at elevated temperatures.…”
Section: Discussionmentioning
confidence: 99%